2013
DOI: 10.1590/0037-8682-1579-2013
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to severe dengue during an epidemic in Vitoria, State of Espirito Santo, Brazil, 2011

Abstract: Introduction:The prognosis of dengue depends on early diagnosis and treatment, which can help prevent severe forms whose characteristics were evaluated here. Methods: A cross-sectional study was conducted involving dengue cases in Vitória, State of Espírito Santo, Brazil, in 2011. Results: Two health regions registered 56.3% of 371 cases of severe dengue. Of these cases, 21.3% presented with dengue hemorrhagic fever. There were associations between dengue hemorrhagic fever with younger ages and a longer time b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
(6 reference statements)
1
8
0
7
Order By: Relevance
“…Though no significant association was found between age and severity of dengue in our study, Shah I et al and Rachel C et al found younger age as one of the predictive markers for Dengue shock syndrome and dengue hemorrhagic fever. 16,17 1.43:1 was the male: female ratio in our study, similar to study by Rasul et al 15 Though studies by Anders KL et al and Phuong CX et al found increased risk of shock and death among females, our study did not have a significant association similar to studies by Pongpan S and Ahmed FU et al [18][19][20][21] No significant association was found between the nutritional status of the study subjects and the severity of dengue fever. Pichainarong stated that severe dengue is rarely seen in children with protein energy malnutrition.…”
Section: Discussionsupporting
confidence: 88%
“…Though no significant association was found between age and severity of dengue in our study, Shah I et al and Rachel C et al found younger age as one of the predictive markers for Dengue shock syndrome and dengue hemorrhagic fever. 16,17 1.43:1 was the male: female ratio in our study, similar to study by Rasul et al 15 Though studies by Anders KL et al and Phuong CX et al found increased risk of shock and death among females, our study did not have a significant association similar to studies by Pongpan S and Ahmed FU et al [18][19][20][21] No significant association was found between the nutritional status of the study subjects and the severity of dengue fever. Pichainarong stated that severe dengue is rarely seen in children with protein energy malnutrition.…”
Section: Discussionsupporting
confidence: 88%
“…While this classification might be useful for the clinical management of patients, it is known that such predictors of severity may vary according to different epidemiological settings [14,15]. In addition, the evolution to death of severe cases may be related to the presence of clinical and laboratory characteristics that are still not fully understood [16].…”
Section: Introductionmentioning
confidence: 99%
“…A maior incidência de vítimas do sexo feminino também foi observada nos trabalhos de Fernandes et al (2014), Vicente (2013), Souza e Dias (2010), Gonçalves e Rebelo (2004) e Forattini et al (2000).…”
Section: Resultsunclassified